The effect from the increasing of oil price towards the economy in Malaysia / Norleen Zuliati Badrul Hisham (Faculty of Business and Management, 2007)
When the government announces another hike in Malaysia's retail petrol and diesel prices on July 31, 2005, it brings major effects toward Malaysia economics. This was the second hike in retail petrol price and the third for diesel. In total, the government has raised prices of petrol by 20% and diesel by 68.6% since the first hike in May 2004. The increase in domestic fuel prices recently was inevitable given that oil prices in the international market had surpassed the US$60 per barrel in June 2005, a level the authority has earlier hinted (in November 2004) will prompt it to revise the retail oil prices at the petrol pumps. The increasing of oil price giving the large impact to many industries such as automobile, transportation, and machinery in many factory industries. The clear view to us where all the industries are important to generate Malaysia's income. Due to that, in depth research need to be done in order to solve the effect from the increasing of oil price especially towards economics. Three main points that we can measure by looking at gross domestic product (GOP), inflation and government spending. Due to that, researcher wants to identify how the factors affect from the increasing of oil price towards the economy in Malaysia. Beside that, to suggest and make recommendation to solve all the problem mentioned. Researcher has used secondary data or previous study for this research which include government publications of economic indicators, statistical and books and periodicals. All secondary data are processed and analyzed using Statistical Package for Social Science (SPSS Version 11.0). In conclusion, to study the effect from the increasing of oil price towards the economy in Malaysia, researcher has analyze from the previous study and found that the 3 factors that have been discussed are relevant and from the interpretation of data, the entire research objective successfully achieved.